Kadar Kolesterol Total Pada Pengguna KB Suntik Tiga Bulan - Ramadani, Debi; Mus, Rosdiana; Sugrani, Andis; Abbas, Mutmainnah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Three-month injectable contraception is a type of hormonal contraception, which contains 150 mg Depo Medroxyrogesterone Acetate (DMPA) which is given every three months. Depo Medroxyrogesterone Acetate can reduce HDL cholesterol levels and can increase LDL levels. This study aims to determine cholesterol levels in three-month injection contraceptive users at the Kassi Kassi Community Health Center. The research design used was descriptive, in which respondents used injectable contraceptives for more than 1 year of use with a sample taken of 15 respondents using a purposive sampling technique with the inclusion criteria of subjects willing to be used as research samples, using 3-month injectable contraceptives for more than 1 year, aged 25 – 35 years old and fast for 8 – 10 hours. The research was conducted at the Kassi Kassi Health Center and Megarezky Makassar clinic in November 2021. The research results were obtained from 15 respondents, there were 6 respondents (40%) with normal cholesterol levels, and there were 9 respondents (60%) with high cholesterol levels. The conclusion is that the majority of 3-month injection contraceptive users have high cholesterol levels.